Kerjasama Ekonomi Bilateral Indonesia dan Malaysia dalam Sektor Komoditi Kelapa Sawit Tahun 2006-2010 - Hakim, Al-Kharitza Rahman (Global and Policy Journal of International Relations, 2014)
ABSTRACTBilateral economic cooperation had been made between Indonesia and Malaysia to respondglobal demand on crude palm oil as a trade commodity. This study uses demand theory, theconcept of bilateral economic cooperation, and interdependence to analyze the case. This studyalso uses quantitative-descriptive to process the data. The research question of this study iswhat causes the signed of the MoU 2010 between Indonesia and Malaysia? The MoU is dealingwith the negative campaign of the crude palm oil commodity. Before the MoU 2010, bothgovernment had been had cooperation on investment, workers, and land reform. BothIndonesia and Malaysia are also very aware in the potential of the crude palm oil as a tradecommodity, thus they drove bilateral cooperation to ensure their exports to other countries.Theses negative campaigns and negative issues are the catalysts on the sign of the MoU 2010between Indonesia and Malaysia.Keywords: Indonesia, Malaysia, Bilateral Economic Cooperation, Crude Palm OilDOI:https://doi.org/10.33005/jgp.v2i02.2067